Strategy for Improving the Competitiveness of Shipyards in the Eastern Part of Indonesia - Baso, Suandar; Musrina, M; Anggriani, Andi Dian Eka (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2020)
In recent years, the number of shipyards in Indonesia has increased significantly to anticipate the increasing demand and the government policy regarding the Cabotage Principles and Masterplan for Acceleration and Expansion of Indonesia’s Economic Development (MAEIED), and three Archipelagic Sea-Lanes (ASL’s) in Indonesia. However, shipbuilding and ship repair works have been centered in the western part of Indonesia. Therefore, this study aims to develop a potential strategy of shipyards in the eastern part of Indonesia to compete in the current market situation. The Analytical Hierarchy Process (AHP) method was used to model the strategy hierarchy and analyze the weight of sub-criteria as the internal and external factors of the shipyard competitiveness. Then, the Blue Ocean Strategy method was used to analyze the competitiveness strategy. To improve competitiveness, the shipbuilding industries in the eastern part of Indonesia have to focus intensively on reforming and upgrading several internal environment factors such as coordination and response, business network, high skill manpower, and complex ship types building ability. Besides, the shipyards also have to focus on external environmental factors, particularly on five factors that have a high influence on improving competitiveness, namely shipping company partners, networks and partnership with suppliers, government policies, human resource development, and cluster formation of shipyards.